Pengaruh Manajemen Aset Terhadap Optimalisasi Pemanfaatan Aset Tetap (Study Kasus Pada Pemerintah Kabupaten Barito Kuala) - Jadid, Achmad Nur; Hifni, Syaiful; Rosari, Novika (Mutiara: Multidiciplinary Scientifict Journal, 2024)
This study aims to determine the effect of Asset Management on Optimizing the Utilization of Fixed Assets. This is causal research using a quantitative approach. The research subject is the SKPD of the Barito Kuala Regency Government. The sample of which was determined using the purposive sampling technique to collect data. The data source used is primary data. The analytical method used is multiple linear regression analysis. The results of the study conclude that: (1) Asset inventory has a significant effect on optimizing the utilization of fixed assets, (2) Legal audit has a significant effect on optimizing the utilization of fixed assets, (3) Asset valuation has a significant effect on optimizing the utilization of fixed assets, and (4) Supervision and control significant effect on optimizing the utilization of fixed assets.